Competency-based medical education and scholarship: Creating an active academic culture during residency - Bourgeois, James A. (Perspect Med Educ, 2015)
The competency-based medical education movement has been adopted in several medical education systems across the world. This has the potential to result in a more active involvement of residents in the educational process, inasmuch as scholarship is regarded as a major area of competency. Substantial scholarly activities are well within the reach of motivated residents, especially when faculty members provide sufficient mentoring. These academically empowered residents have the advantage of early experience in the areas of scholarly discovery, integration, application, and teaching. Herein, the authors review the importance of instituting the germinal stages of scholarly productivity in the creation of an active scholarly culture during residency. Clear and consistent institutional and departmental strategies to promote scholarly development during residency are highly encouraged.